Ontologi, epistemologi, dan aksiologi dalam ilmu geografi: Sebuah kajian interdisipliner untuk memahami hubungan manusia dan lingkungan - FA IZAH, ALFINA NUR (Maliki Interdisciplinary Journal, 2025)
Science that includes physical and social aspects. This view causes researchers to often limit themselves to sciences that support geography, and sometimes ignore other branches of science. Geography is often considered a science, but if there is no recognition from other scientists, its existence in the future could be threatened. This research aims to explain human geography from the perspective of the philosophy of science, including aspects of ontology, epistemology and axiology of human geography. Human geographic ontology is an integral part of geographic science. The methods used in landscape analysis are complex, including dimensions of geography, environment and geography itself. In terms of epistemology, human geography uses qualitative and quantitative approaches based on comprehensive research. From an axiological perspective, the existence of human geography is very important because it contributes to development.